Spatial rogue waves in quadratic optical slab waveguides - Schiek, Roland; Setzpfandt, Frank; Pertsch, Thomas; Baronio, Fabio; De Angelis, Costantino (Optics InfoBase Conference Papers, 2018)
Spatial optical breather solutions of the Nonlinear Schro¨dinger Equation have been observed for the first time. The experiment was performed in an optical slab waveguide with the cascaded quadratic nonlinearity in second-harmonic generation.
CRIS-Team Scopus Importer:2023-04-20